Revealing the Toxicity-Enhancing Essence of Glycyrrhiza on Genkwa Flos Based on Ultra-high-performance Liquid Chromatography Coupled With Quadrupole-Orbitrap High-Resolution Mass Spectrometry and Self-Assembled Supramolecular Technology - Yuqin Yang; Feifei Li; Mengmeng Yan; Shan Chen; Desheng Cai; Xiaojing Liu; Nana Han; Zhihua Yuan; Jihui Lu; Yaozhi Zhang; Qiang Ma; Penglong Wang; et al. (Frontiers in Chemistry, 2021)
Researchers often focus on the mechanisms of synergistic agents, a few explore drug combinations that enhance toxicity, while few have studied the internal mechanism of compatibility enhancement in chemical level. Herein, we present a comprehensive analysis based on ultra-high-performance liquid chromatography coupled with quadrupole-Orbitrap high-resolution mass spectrometry (UHPLC-Q-Orbitrap HRMS) and a self-assembled supramolecular strategy, which reveals the toxicity-enhancing essence of glycyrrhizic acid originated in licorice when combined with Genkwa Flos. Through this method, we discovered the toxicity was enhanced through the formation of a supramolecular complex from Genkwa Flos/glycyrrhizic acid. The morphology and size distribution of the self-assembled nanoparticles were characterized by scanning electron microscopy and dynamic light scattering Furthermore, a total of 58 constituents (eight diterpenoids, 35 flavonoids, five phenylpropanoids, four nucleosides, two amino acids, and four other compounds) consisted from the supramolecular complex were identified through accurate-mass measurements in full-scan MS/data-dependent MS/MS mode. Based on the hydrophobic interaction of glycyrrhizic acid with yuanhuacine (one of main ingredients from Genkwa Flos), the supramolecular self-assembly mechanism was revealed with proton nuclear magnetic resonance (1H-NMR) and NOESY 2D NMR. The toxicity of Genkwa Flos and Genkwa Flos/glycyrrhizic acid supramolecular complex were compared through in vitro studies on L-02 cells using a 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay; and 4′,6-diamidino-2-phenylindole (DAPI) staining was performed to further confirm the enhancement inhibition of Genkwa Flos/glycyrrhizic acid supramolecular complex than Genkwa Flos. This study provides fundamental scientific evidence of the formation of a self-assembled phytochemical supramolecular when Genkwa Flos and glycyrrhizic acid are combined, enabling to understand their clinical incompatibility and contraindication.